Gender-Stereotyped Barriers Against Women Football Players in Turkey: A Qualitative Perspective on the Eccles' Expectancy-Value Theory - F. Hülya Aşçı; Safter Elmas (Pamukkale University, 2022)
This qualitative research aimed to investigate the experiences of women football players in Turkey in terms of Eccles' Expectancy-Value Theory from a gender stereotypes perspective. A phenomenological method was used to allow a deeper understanding of their experiences. The research group consisted of eight women from three different football league levels in Istanbul, TR. The data were analyzed via thematic and content analysis. The identified themes after content analysis are: (1) loving football; (2) instrumentality of football; (3) sociocultural barriers against women players; (4) multidimensional perceived costs. According to these findings, we can illustrate that the social, cultural, and institutional environment of the women players creates many problems, difficulties, and deprivations in their participation, which make it difficult for their expectancy for success, task values, and future plans in their sports. In order to make the experiences of female football players about gender-based stereotypes more understandable, it is recommended that more studies that deal with the qualitative method and Eccles' theory should be done in future studies.